Studies on Stigma Receptivity and Pollen Viability in Parental Lines of Phule Aadishakti Hybrid of pearlmillet as Affected by Different Seasons - TJ JADHAV; PY SHINDE; MT BHINGARDE; KK BARHATE; DS THAKARE (Seed Research, 2025)
Stigma receptivity and pollen viability are critical determinants of successful hybrid seed productionin pearl millet (Pennisetum glaucum (L.) R. Br.), particularly in male-sterility–based hybrid breeding systems. Thepresent investigation was undertaken to study the effect of seasons on stigma receptivity and pollen viability inparental lines of the Phule Aadishakti pearl millet hybrid during Kharif and summer seasons. The experimentalmaterial comprised the male-sterile line DHLB-8A (female parent), the maintainer line DHLB-8B, and the restorerline DHLB-967 (male parent). Stigma receptivity was evaluated under six starvation interval treatments (0, 1, 2, 3,4, and 5 days), while pollen viability was assessed at six pollination intervals (0, 2, 4, 6, 8, and 10 hours). Seed setpercentage, number of seeds per earhead, seed weight per earhead, and 1000-seed weight were recorded toassess reproductive success. Results revealed that both stigma receptivity and pollen viability were significantlyinfluenced by season, with superior performance observed during the Kharif season compared to the summerseason. Higher seed set and yield attributes in Kharif indicated more favorable environmental conditions forreproductive processes. The findings highlight the importance of optimizing season-specific floweringsynchronization and pollination timing for efficient hybrid seed production. This study provides valuable insightsfor improving seed yield and quality in pearl millet hybrid breeding and commercial seed production programs.